Construction of Islamic Boarding School Identity: Principal's Strategy and Leadership Style in Institutional Transformation - Fatimah Khoirunnisa; Nurul Latifatul Inayati (JIE (Journal of Islamic Education), 2026)
Pesantren as traditional Islamic educational institutions face challenges in building an institutional identity in the era of globalisation, especially for newer pesantren that lack social legitimacy, a track record, and a strong organisational culture. This situation demands strategic and adaptive leadership from principals in managing institutional transformation and building public trust. This study aims to analyse the principal's strategies and leadership styles in building the identity of the Muharrikun Najaah Islamic Boarding School in Klaten Regency and identify the obstacles encountered. The study used a qualitative approach with a case study design. The study draws primary data from the principal and senior teachers and secondary data from internal institutional documents. It collects data through semi-structured interviews, document analysis, and non-participant observation. The researchers conducted the data analysis using thematic and inductive approaches and validated the findings through triangulation of sources and methods. The results indicate that identity construction is carried out multidimensionally through four main strategies: structural through the integration of formal education (MTs and MA) for legitimacy; practice-based through flagship programs such as PMPT (persiapan masuk perguruan tinggi) and development of student talents (lingkaran sore); humanistic through teacher empowerment within a distributed leadership framework; and cultural through the internalisation of Islamic values, discipline, and character. The leadership style applied is semi-authoritative, with a top-down approach that maintains limited participation and emphasises role modelling. Barriers include resistance to change, change fatigue, human resource dynamics, the complexity of system integration, and external pressures. These findings have implications for strengthening adaptive leadership in building a sustainable Islamic boarding school identity.